2021
DOI: 10.3390/electronics10141740
|View full text |Cite
|
Sign up to set email alerts
|

GaborPDNet: Gabor Transformation and Deep Neural Network for Parkinson’s Disease Detection Using EEG Signals

Abstract: Parkinson’s disease (PD) is globally the most common neurodegenerative movement disorder. It is characterized by a loss of dopaminergic neurons in the substantia nigra of the brain. However, current methods to diagnose PD on the basis of clinical features of Parkinsonism may lead to misdiagnoses. Hence, noninvasive methods such as electroencephalographic (EEG) recordings of PD patients can be an alternative biomarker. In this study, a deep-learning model is proposed for automated PD diagnosis. EEG recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…The first convolutional layer contain numerous filters which extract features from the input image to generate multiple feature maps. The subsequent pooling and convolutional layers reduce the dimension of the feature maps and further enhance the features, thereby reducing the complexity of the feature map and the likelihood of overfitting [25]. This could be considered as analogous to the human visual system, where the visual cortex attempts to break down images into simpler representations for the brain to perceive the image with ease [24].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
See 2 more Smart Citations
“…The first convolutional layer contain numerous filters which extract features from the input image to generate multiple feature maps. The subsequent pooling and convolutional layers reduce the dimension of the feature maps and further enhance the features, thereby reducing the complexity of the feature map and the likelihood of overfitting [25]. This could be considered as analogous to the human visual system, where the visual cortex attempts to break down images into simpler representations for the brain to perceive the image with ease [24].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…After the final pooling layer, the feature maps are converted into single-list vectors at the flatten layer (Figure 2). The neurons in the neural networks, also known as the fully connected layers, will then learn to recognize the features from the single-list vectors and perform image classifications [25]. Hence, CNN models are known for their exemplary image recognition ability, which many studies have successfully demonstrated the success of CNN in medical imaging, including the recognition of breast tumors, and eye diseases using mammogram and color fundus images, respectively [26].…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…[51,64,66,70] using ANN with values over 97% for sensitivity and precision, refs. [38,39,49] considering CNN with values over 99% for accuracy, precision and sensitivity ( [38,39] were based on the same study), refs. [29,30] using CNN + RNN with values over 93% in accuracy, sensitivity, and precision, refs.…”
Section: Evaluation Of the Models Usedmentioning
confidence: 99%
“…Therefore, there is a growing need for brain-computer interface (BCI) systems for healthy elderly persons going through nonpathological physical and cognitive declines [30,52]. BCI systems connect the brain to a computer, allowing the user to enhance their life [23,51]. As machine learning and intelligent robotic technology advance, the range of BCI applications is growing.…”
Section: Introductionmentioning
confidence: 99%